Development of an improved acm scheme for mitigating earth-to-space propagation effects - Tekanyi, A. M. S.; Idris, R. M.; Usman, A. D.; Abdullahi , M. Z.; Agbon, E. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Satellite communication is a promising technology due to its ability to serve very large number of users with high data rate services. The communication link experiences propagation losses such as: Path loss, atmospheric losses, rain fading, ionosphere effects (such as scintillation), and other effects which can greatly affect the received signal strength and close the link budget in the worst case. The design of future broadband satellite systems has to be done with the challenge of more complex traffic mix and these harsher propagation conditions which mitigate the performance of the communications link. Link adaptation (LA) has been used in satellite communications applications for evaluating the performance of an adaptive modulation system in the unique space-based propagation environment. Despite the current research on improving satellite system performance, there is still a need to further develop a scheme that mitigates the effect of atmospheric impairments. This work develops an improved adaptive coding and modulation scheme that mitigates earth-to-space propagation effects. The scheme targets maximizing data throughput while staying below a Bit Error Rate (BER) threshold so as to successfully mitigate link impairment in fixed communication systems. Simulation of the work is carried out using MATLAB 2016b and System Toolkit (STK) 11.3